Perceptions of Whether Stereotypic Off-the-Track Thoroughbreds are Harder to Rehome Than Nonstereotypic OTTBs—A Pilot Survey Study - Wickens, Carissa L. (2019)
Several studies have indicated higher incidence of stereotypic behaviors (STBs) in Thoroughbreds. The aftercare of Off-the-Track Thoroughbreds (OTTBs) has received increased attention in the last decade; however, research on the impact of STBs on placement of OTTBs after their racing career is limited. Thoroughbred Aftercare Alliance (TAA) accredits centers throughout North America that work to rehome OTTBs in a safe, welfare-friendly manner. Although the authors have suspected that having an STB would make OTTBs more challenging to rehome, this hypothesis remains to be empirically tested. The objec tives of the present study were to investigate STB in OTTBs among TAA-accredited centers throughout the U.S. and to characterize perceptions of STB among OTTB owners. Using an openly available online database, we contacted 54 centers using mixed mode, multiple contact survey methods. Thirty-eight centers responded (70% response rate) representing 987 OTTBs taken in over the past year. Of the accepted horses, respondents stated that 17% (n ¼ 172) had one or more STBs. Ninety-two percent of centers indicated having an STB made horses somewhat/much more challenging to rehome (P < .0001; c2 ; df ¼ 4). One hundred current and prospective owners responded to a second survey administered through the OTTB Connect Facebook page. Fifty-five percent of respondents currently owned an OTTB with an STB, and 45% of respondents indicated having an STB would negatively impact their decision to purchase or adopt their next OTTB. While we recognize there are limitations in interpreting self-reported survey data, the findings suggest STBs may impede adoption of OTTBs.